The Effects of Vocabulary Development on Text Comprehension - Wong Bee Eng; Mardziah Hayati Abdullah (The English Teacher, 2003)
The study reported in this paper adopts three strategies — knowledge and use of context clues, doing structural analysis and making associations — to help ESL learners improve their vocabulary knowledge and hence their text comprehension. Forty-six secondary school ESL students participated in the study. The treatment took the form of explicit strategy instruction to acquire word meaning of selected vocabulary items from reading texts. A comparison of mean scores enabled the researchers to determine the effectiveness of vocabulary development strategies in the ESL reading classroom.